التحليل الاقتصادي القياسي لدوال إنتاج الفريز في محافظة طرطوس، سورية (Journal of Hama University, 2024)
The research was conducted in Tartous Governorate for the agricultural season 2020/2021 through a simple random sample consisting of 360 farmers from strawberry growers in Tartous Governorate. Production function using the Cobb-Douglas model to identify the most important factors affecting strawberry production. The results of the research showed that the independent factors, the number of houses, the amount of nitrogen fertilizers, and the amount of fruit rot pesticides included in the model had a significant effect on the dependent variable (production), the amount of phosphorus fertilizer, and the amount of nitrogen fertilizer included in the model had a significant effect on the dependent variable. The results of the research also showed that the coefficient of determination (R2) was about 82.1% and 65.4% in the protected and open cultivation, respectively, and the total productive elasticity was about 0.83 and 1.34 for the protected and open cultivation, respectively.The research recommended the necessity of urging strawberry farmers, whether in protected or open cultivation, to pay attention to the productive elements that most affect strawberry productivity, especially fungicides, the number of houses, in addition to organic and potassium fertilizers.
Keywords: Strawberries; protected agriculture; open cultivation; production functions; flexibility of productive elements; Cobb-Douglas; Tartous; independent variables; dependent variable